Application of the Analytic Hierarchy Process in the choice of health insurance (Research, Society and Development, 2019)
The contemporary world we live in leads us to a constant pace of life and diverse needs, so when it comes to medical care, the needs are very diverse. For this reason, when looking for a health plan, several factors need to be considered in order to make a decision, such as coverage that works with personal and family life, number of available care units, location of these units, and , an attractive cost-benefit ratio. This article aims to present a proposed approach to identify factors that users consider as most relevant in choosing a health plan service. The Multicriteria Analytic Hierarchy Process (AHP) was used to help identify the relevant factors used in the selection of health plans. And, as a research unit, an application was carried out with a group of users, with the intention of understanding the perspectives as decision makers. As a result, when a dynamic sensitivity analysis was performed, it was observed that the factors considered most relevant at the moment of decision making were quality and speed of care, these received the highest weights, 33.9% and 23.6% , respectively. The proposed approach provides an important planning and operating tool for health plan operators, who are then able to examine which factors are considered most important in their visions and thus formulate competitive strategies and market positioning.